2014
DOI: 10.1088/2041-8205/791/2/l24
|View full text |Cite
|
Sign up to set email alerts
|

EQUATORIAL ZONAL JETS AND JUPITER's GRAVITY

Abstract: The depth of penetration of Jupiter's zonal winds into the planet's interior is unknown. A possible way to determine the depth is to measure the effects of the winds on the planet's high-order zonal gravitational coefficients, a task to be undertaken by the Juno spacecraft. It is shown here that the equatorial winds alone largely determine these coefficients which are nearly independent of the depth of the non-equatorial winds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…It should be pointed out that the approach using the TWE or the TGWE is profoundly different from another approach that makes the barotropic assumption-the density ρ in fully compressible gaseous planets is a function only of the pressure p. The barotropic model was adopted to study the effect of deep zonal winds on Jupiter's gravitational harmonics in spherical geometry (Hubbard 1999) and in non-spherical geometry (Kong et al 2013a(Kong et al , 2014. There are at least four significant differences between the two different approaches.…”
Section: Introductionmentioning
confidence: 99%
“…It should be pointed out that the approach using the TWE or the TGWE is profoundly different from another approach that makes the barotropic assumption-the density ρ in fully compressible gaseous planets is a function only of the pressure p. The barotropic model was adopted to study the effect of deep zonal winds on Jupiter's gravitational harmonics in spherical geometry (Hubbard 1999) and in non-spherical geometry (Kong et al 2013a(Kong et al , 2014. There are at least four significant differences between the two different approaches.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the assumptions that the rotational effect upon the Jovian shape is negligibly small and that the observed cloud-level zonal winds extend on the cylinders, but decay exponentially in the radial direction, Kaspi et al (2010) solved the thermal-wind equation to estimate the wind-induced density anomaly and the corresponding gravitational correction DJ n with n even and  n 2. By assuming that Jupiter is in the shape of an oblate spheroid and that the observed cloud-level zonal winds extend all the way on the cylinders from the northern to the southern hemisphere without being blocked by the Jovian magnetic field, Kong et al (2013a) computed the variation of the Jovian gravitational coefficients ΔJ 2 , ΔJ 4 ,..., ΔJ 12 caused by the effect of the zonal winds, while Kong et al (2014) revealed the dominance of the equatorial zonal jets in determining the high-order gravitational coefficients. Furthermore, the Jovian magnetic field is generated by convection-driven motion in its deep metallic region that must be non-axisymmetric, but whose amplitude and structure are unknown; Kong et al (2016) discussed a promising way of probing the Jovian convective dynamo via its effect on the external non-axisymmetric gravitational field.…”
Section: Introductionmentioning
confidence: 99%
“…An important objective of the Juno spacecraft is to probe the extent of penetration of the zonal winds into the interior of Jupiter by accurately measuring their effects on its gravitational field with unprecedentedly high precision. Since the high-order coefficients J n with even n are found to be nearly independent of the depth of the zonal winds in the non-equatorial regions (Kong et al 2014), and since the size of J n with odd n are directly related to the depth of the equatorially antisymmetric zonal winds (Kaspi 2013), accurately determining the odd coefficients J n in equation (1) would play a critical role in understanding the structure of the zonal winds in the deep interior of Jupiter.…”
Section: S U M M a Ry A N D R E M A R K Smentioning
confidence: 99%
“…In a recent study, Kong et al (2014) computed the gravitational signature produced by the Jovian equatorial winds that are equatorially symmetric and confined within a small equatorial region between the latitudes ϕ = ±25…”
mentioning
confidence: 99%
See 1 more Smart Citation